Progesterone, inflammation and preterm labor - Pařízek, Antonín; Koucký, Michal; Dušková, Michaela (The Journal of steroid biochemistry and molecular biology, 2014)
The initiation of human parturition is not fully understood to date. The data from animal experiments demonstrate that the primary impulse for the initiation of physiological labor arises from the fetal hypothalamo-pituitary-adrenal axis (HPA). HPA is responsible for the stimulation of steroid synthesis and prostaglandin production and, in turn, the cervical dilation and the beginning of myometrial contractions. Animal experiments, however, are only partly suitable for understanding the mechanism of human labor due to substantial species-specificity. In human, the changing levels of placental CRH control the production of fetal and placental steroids. The fundamental pathogenic manifestation of spontaneous preterm labor is inflammation and similar processes also underlie the full term one. While in full term labor it is not yet precisely known what starts this process, in the preterm one, several factors have been discussed like infection, uteroplacental ischemia, and hormonal abnormalities (progesterone- or CRH-related). Inflammatory processes affect both the mother and the fetus. Fetal inflammatory response (FIRS), which can be expected for children born preterm, is frequently associated with long-term complications, in particular neurological and pulmonary. Research in this field is therefore aimed at predicting preterm labor, and on predicting the fetal inflammatory response. The role of progesterone and its receptors in the pathophysiology of preterm labor are likewise intensively studied. Clinical results on the use of additive doses of progesterone in secondary prevention of preterm labor and current experimental studies point to progesterone and its receptors playing a key role in the pathophysiology of preterm labor. This article is part of a Special Issue entitled 'Pregnancy and Steroids'.
Keywords: Inflammation Mediators; progesteron; Pregnancy; Animals; předčasná porodní činnost; mediátory zánětu; Humans; Preterm birth; CRH; Female; ženské pohlaví; zvířata; Human; Inflammation; Obstetric Labor, Premature; zánět; lidé; těhotenství; Progesterone